2011
DOI: 10.1182/blood-2011-08-367466
|View full text |Cite
|
Sign up to set email alerts
|

Publication bias is present in blood and marrow transplantation: an analysis of abstracts at an international meeting

Abstract: Publication bias is the preferential publication of research with positive results, and is a threat to the validity of medical literature. Preliminary evidence suggests that research in blood and marrow transplantation (BMT) lacks publication bias. We evaluated publication bias at an international conference, the 2006 Center for International Blood and Marrow Transplant Research (CIBMTR)/American Society for Blood and Marrow Transplantation (ASBMT) "tandem" meeting. All abstracts were categorized by type of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…The publication ratio from the 2006 ACR/ARHP Annual Scientific Meeting was comparable to other scientific meetings from recent years (2001–2007) (7–17) (Table 4). Publication ratios from other meetings varied remarkably between 20.5% and 68.9%.…”
Section: Resultssupporting
confidence: 57%
“…The publication ratio from the 2006 ACR/ARHP Annual Scientific Meeting was comparable to other scientific meetings from recent years (2001–2007) (7–17) (Table 4). Publication ratios from other meetings varied remarkably between 20.5% and 68.9%.…”
Section: Resultssupporting
confidence: 57%
“…; Paulson et al. ), suggests that there is currently no publication bias towards positive results in the veterinary anaesthesia literature, as we found no association between outcome and subsequent publication. It is possible that researchers and reviewers of the specialty of veterinary anaesthesia and analgesia consider negative outcomes as being as important as positive outcomes.…”
Section: Discussioncontrasting
confidence: 40%
“…[28][29][30][31][32] Some studies from academic institutions have shown positive results, but there is most likely a selection bias in the literature as negative results are seldom published. 33 With all these concerns in mind, should we really use stromal cells as treatment for GVHD? Before we condemn this kind of therapy, we will summarize what we know today.…”
Section: Introductionmentioning
confidence: 99%